Cognitive Processes of Opportunity Recognition: The Role of Structural Alignment - Grégoire, Denis A.; Barr, Pamela S.; Shepherd, Dean A. (Organization Science, 2010)
Substantial gains can be made by individuals and organizations adept at detecting new opportunities. But how do business leaders do that concretely? Organization research shows that managers are more inclined to identify threats than opportunities, but it is still not clear why this is the case. Likewise, research points to several factors that may facilitate the recognition of opportunities. Yet empirical observations have been limited by retrospective biases and other conceptual challenges. As a result, key questions remain not only about what factors facilitate the recognition of opportunities, but also about why these factors play such a role. To further understanding of these issues, we study the reasoning strategies that individuals mobilize for recognizing opportunities. We develop a model of opportunity recognition as a cognitive process of structural alignment, and analyze the think-aloud verbalizations of executive entrepreneurs as they try to recognize opportunities for new technologies. In contrast to prior research, the qualitative and quantitative data do not provide evidence that individuals use prototypes to recognize opportunities. Instead, we find that different kinds of mental connections play different roles in the process of recognizing opportunities, with different consequences. We also document why and how prior knowledge may facilitate this process. By drawing attention to the cognitive underpinnings of opportunity recognition, we cast light on why it constitutes such a challenging task for individuals and organizations. In turn, this provides a useful basis for exploring the factors that explain why some individuals/organizations are able to recognize opportunities that others simply fail to see.